2020
DOI: 10.1609/aaai.v34i04.6161
|View full text |Cite
|
Sign up to set email alerts
|

Atari-HEAD: Atari Human Eye-Tracking and Demonstration Dataset

Abstract: Large-scale public datasets have been shown to benefit research in multiple areas of modern artificial intelligence. For decision-making research that requires human data, high-quality datasets serve as important benchmarks to facilitate the development of new methods by providing a common reproducible standard. Many human decision-making tasks require visual attention to obtain high levels of performance. Therefore, measuring eye movements can provide a rich source of information about the strategies that hum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 28 publications
3
22
0
Order By: Relevance
“…An interesting aspect about this approach is that attention is learnt from humans by utilizing the eye tracking data and instead of just utilizing it for evaluation like the previous method [60]. Nikuli et al [2] suggested a quantitative method to evaluate the attention mechanism generated saliency maps by comparing them with the eye tracking data publicly available by [62]. They used their proposed metric to compare different attention based RL models.…”
Section: B: Intrinsic Saliency Mapsmentioning
confidence: 99%
“…An interesting aspect about this approach is that attention is learnt from humans by utilizing the eye tracking data and instead of just utilizing it for evaluation like the previous method [60]. Nikuli et al [2] suggested a quantitative method to evaluate the attention mechanism generated saliency maps by comparing them with the eye tracking data publicly available by [62]. They used their proposed metric to compare different attention based RL models.…”
Section: B: Intrinsic Saliency Mapsmentioning
confidence: 99%
“…Human visual attention data is often obtained using eyetrackers to record their eye movements (gaze). Recently, researchers have collected large-scale human gaze and decision datasets in several visuomotor tasks, such as meal preparation (Li, Liu, and Rehg 2018), human-to-human social interactions (Zuo et al 2018), driving (Palazzi et al 2018), and Atari game playing (Zhang et al 2020b). So far these datasets have been used for modeling human attention.…”
Section: Human Visual Attention Data In Decision-making Tasksmentioning
confidence: 99%
“…We use human expert gaze data from Atari-HEAD dataset (Zhang et al 2020b) due to their semi-frame-byframe data collection protocol. The original game runs continually at 60Hz (Bellemare et al 2013), a speed that is challenging even for professional gamers.…”
Section: Human Attention Data and Modelmentioning
confidence: 99%
See 2 more Smart Citations